A High Rate of Bacteriologic Culture-Positive Findings Is Seen After Revision Rotator Cuff Surgery - Ajith Malige, M.D; Alexandra Boyd, B.S; Isaac Manuputy, B.S; Richard Michelin, D.O; John M. Itamura, M.D (Elsevier, 2023)
Purpose: To determine the incidence of subclinical infections in patients undergoing revision arthroscopic rotator cuff repair and identify any risk factors for developing these infections. Methods: Patients who underwent revision surgery by the senior author between January 2012 and December 2022 after a previous rotator cuff surgery were identified. All patients undergoing an open or arthroscopic revision of their previous rotator cuff surgery were included. Patients who had noted previous shoulder infections or had incomplete chart documentation were excluded. For each patient, demographic information, surgical information, and culture results were recorded. Results: A total of 115 patients were identified. Thirty-nine were excluded due to incomplete chart documentation (35) or a history of infection (4); therefore, 22 patients (28.9%) had positive cultures (31 cultures in total). Seventeen patients had only Cutibacterium acnes identified. C acnes cultures turned positive on average 13.52 days after culture collection. There was no difference in infection incidence rates between isolated rotator cuff repair and rotator cuff repair plus additional surgeries (P = .88) or between initial arthroscopic versus open procedures (P = .83). None of the 12 identified risk factors, including age, sex, race, smoking history, previous corticosteroid injections, malnutrition, renal failure, liver failure, diabetes mellitus, immunocompromised status, intravenous drug use, and number of revisions, were correlated with the presence of a subclinical infection. Finally, 6 patients had control cultures taken. One culture (16.6%) was positive for C acnes, while this patient did not have a positive shoulder culture. Conclusions: Subclinical shoulder infections can be present in more than one-quarter of patients undergoing revision after rotator cuff repair. Level of Evidence: Level IV, diagnostic case series.